PENGARUH MODAL DAN TINGKAT UPAH TERHADAP PENYERAPAN TENAGA KERJA DILIHAT DARI PERSPEKTIF EKONOMI ISLAM PADA INDUSTRI TEKSTIL DI KECAMATAN MEDAN KOTA (Studi Kasus: Mahasiswa UIN-SU Program Studi Ekonomi Islam Angkatan 2016) - Debby Nadillah Harahap; Fauzi Arif Lubis; Aqwa Naser Daulay (Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to determine the effect of local own source revenue, fiscal balance This study aims to examine the effect of capital and influence on the application of labor in the textile industry in Medan Kota District. This type of research uses quantitative research using data from the Department of Industry, data from the Central Statistics Agency (BPS). This study uses the Eviews 7.0 assistance program. The analysis used in this research is panel data analysis in which Wages, Capital as independent variables and Labor Absorption as dependent variables. The results showed that the results of panel data estimation with the Fixed Effect Model (FEM) explained that simultaneously capital and wage levels had a significant effect on employment in the textile industry in the district of Medan Kota at a confidence level of 95 percent. While partially the estimation results of panel data with Fixed Effect Model (FEM) explain that capital has no significant effect on employment in the textile industry in the district of Medan Kota. The level of increase has a significant and positive effect on employment in the textile industry in the district of Medan Kota.